Peningkatan Kemampuan Operasi Penjumlahan Melalui Model Pembelajaran Discovery Learning bagi Anak Disabilitas Intelektual Ringan - Defitrianda, Defitrianda; Iswari, Mega; Damri, Damri; Nasri, Yosa Yulia (Jurnal Pendidikan Madrasah, 2026)
This research was motivated by the low ability of students with mild intellectual disabilities in performing addition operations at SLBN Merangin. The study aimed to describe the implementation process and examine the effectiveness of the Discovery Learning model in improving students’ ability to perform addition operations of natural numbers with results up to 10. The research employed a Classroom Action Research (CAR) method using both qualitative and quantitative approaches. The subjects consisted of three third-grade students with mild intellectual disabilities. The study was conducted in two cycles, each including planning, implementation, observation, and reflection stages. Data was collected through observation and performance tests, while data analysis used qualitative and quantitative descriptive techniques in the form of percentages. The findings indicated a significant improvement in students’ addition operation skills in each cycle. In the preliminary condition, the achievement scores of students RA, RDR, and MK were 55%, 40%, and 45%, respectively, which were categorized as requiring substantial assistance. After the implementation of Cycle II, their scores increased significantly to 85% for RA, 82% for RDR, and 80% for MK, all of which met and exceeded the Learning Achievement Criteria (KKTP) of 76%. Therefore, the Discovery Learning model proved effective in enhancing students’ active participation, conceptual understanding, and independence in performing addition operations using concrete objects.